Biopsychosocial determinants of anxiety and depression among working mothers in China: A public mental health perspective - Jiao, Jia; Jenraumjit, Rewadee; Worland , Shirley; Bunyachatakul , Saifon; He, Bijing; Wongpakaran, Tinakon (Narra J, 2025)
Working mothers often face dual demands from work and parenting, increasing their risk for anxiety and depression. However, the prevalence and contributing factors among Chinese working mothers remain underexplored. The aim of this study was to examine the prevalence and biopsychosocial determinants of anxiety and depression in this population. A cross-sectional survey was conducted between October 17 and November 21, 2024 through WeChat online among 330 working mothers aged 30–45 years old using validated instruments, including the Outcome Inventory-21 (OI-21), Parental Stress Scale (PSS), Experiences in Close Relationships-revised (ECR-R-10), Inner Strength-based Inventory (I-SBI), and the Multidimensional Scale of Perceived Social Support (MSPSS). Sociodemographic, socioeconomic and biological factors, including age, marital status, annual income, and physical disease, were also collected through a self-administered general information questionnaire. Data were analyzed using t-test, analysis of variance, Pearson’s correlation, and hierarchical linear regression. This study found the prevalence was 26.1% for anxiety symptoms and 38.2% for depression symptoms in this group based on the screening tools. Anxiety was significantly associated with both biological (e.g., hormonal changes, family psychiatric history) and psychological factors (e.g., attachment anxiety, parental stress). At the same time, depressive symptoms were primarily predicted by psychological and lifestyle-related factors (e.g., smoking, alcohol use). Notably, inner strength was a protective factor across both conditions. The findings highlight the importance of early detection and integrative care strategies for addressing mental health concerns in working mothers. Incorporating psychological screening, lifestyle assessment, and resilience-building interventions into workplace and community-based healthcare services may improve work-family balance outcomes in this population.